Including Health Economic Analysis in Pilot Studies: Lessons Learned from a Cost-Utility Analysis within the PROSPECTIV Pilot Study. Issue 1 (2017) - Burns, Richéal M.; Wolstenholme, Jane; Shinkins, Bethany; Frith, Emma; Matheson, Lauren; Rose, Peter W.; Watson, Eila
Purpose: To assess feasibility and health economic benefits and costs as part of a pilot study for a nurse-led, psychoeducational intervention (NPLI) for prostate cancer in order to understand the potential for cost effectiveness as well as contribute to the design of a larger scale trial. Methods: Men with stable prostate cancer post-treatment were recruited from two cancer centres in the UK. Eighty-three men were randomised to the NLPI plus usual care or usual care alone (UCA) (42 NLPI and 41 UCA); the NLPI plus usual care was delivered in the primary-care setting (the intervention) and included an initial face-to-face consultation with a trained nurse, with follow-up tailored to individual needs. The study afforded the opportunity to undertake a short-term within pilot analysis. The primary outcome measure for the economic evaluation was quality of life, as measured by the EuroQol five dimensions questionnaire (EQ-5D) (EQ-5D-5L) instrument. Costs (£2014) assessed included health-service resource use, out-of-pocket expenses and losses from inability to undertake usual activities. Results: Total and incremental costs varied across the different scenarios assessed, with mean cost differences ranging from £173 to £346; incremental effect, as measured by the change in utility scores over the duration of follow-up, exhibited wide confidence intervals highlighting inconclusive effectiveness (95% CI: -0.0226; 0.0438). The cost per patient of delivery of the intervention would be reduced if rolled out to a larger patient cohort. Conclusions: The NLPI is potentially cost saving depending on the scale of delivery; however, the results presented are not considered generalisable.